The Influence of Service Quality, Trust, and Commitment on Customer Loyalty of Bank Syariah Indonesia KCP Medan Pulo Brayan - Alfina Rahma Wani; Yenni Samri Juliati Nasution; Nur Ahmadi Bi Rahmani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this research is to determine the effect of service quality, trust and commitment to customer loyalty of Bank Syariah Indonesia (BSI) KCP Pulo Brayan Medan. This research uses quantitative research with descriptive research type, where the object of research is Bank Syariah Indonesia (BSI) KCP Pulo Brayan Medan customers. The method in this study is in the form of distributing questionnaires which aims to test and analyze the effect of service quality, trust and commitment to customer loyalty of Bank Syariah Indonesia (BSI) KCP Pulo Brayan Medan. The findings of this study indicate that service quality, trust and commitment affect the loyalty of Bank Syariah Indonesia (BSI) KCP Pulo Brayan Medan customers.